Menstrual Cycle Irregularity in Adolescence Is Associated With Cardiometabolic Health in Early Adulthood - Kate Keenan; Alison E. Hipwell; Tamar S. Polonsky (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Menstrual cycle irregularities are associated with cardiovascular and cardiometabolic disease. We tested associations between age at menarche and cycle irregularity in adolescence and cardiometabolic health in early adulthood in a subsample from the Pittsburgh Girls Study. Methods and Results Data from annual interviews were used to assess age at menarche and cycle irregularity (ie, greater or less than every 27–29 days) at age 15 years. At ages 22 to 25 years, cardiometabolic health was measured in a subsample of the Pittsburgh Girls Study (n=352; 68.2% Black), including blood pressure, waist circumference, and fasting serum insulin, glucose, and lipids. T tests were used for continuous data and odds ratios for dichotomous data to compare differences in cardiometabolic health as a function of onset and regularity of menses. Early menarche (ie, before age 11 years; n=52) was associated with waist circumference (P=0.043). Participants reporting irregular cycles (n=50) in adolescence had significantly higher levels of insulin, glucose, and triglycerides, and higher systolic and diastolic blood pressure (P values range from 0.035 to 0.005) and were more likely to have clinical indicators of cardiometabolic predisease in early adulthood compared with women who reported regular cycles (odds ratios ranged from 1.89 to 2.56). Conclusions Increasing rates and earlier onset of cardiovascular and metabolic disease among women, especially among Black women, highlights the need for identifying early and reliable risk indices. Menstrual cycle irregularity may serve this purpose and help elucidate the role of women's reproductive health in protecting and conferring risk for later cardiovascular and cardiometabolic diseases.